Peer Review system: A Systematic Review - Lasker, Shamima Parvin (Bangladesh Journal of Bioethics, 2018)
Peer review process helps in evaluating and validating of research that is published in the journals. U.S. Office of Research Integrity reported that data fraudulence was found to be involved in 94% cases of misconduct from 228 identified articles between 1994–2012. If fraud in published article are significantly as high as reported, the question arise in mind, were these articles peer reviewed? Another report said that the reviewers failed to detect 16 cases of fabricated article of Jan Hendrick Schon. Superficial peer reviewing process does not reveals suspicion of misconduct. Lack of knowledge of systemic review process not only demolish the academic integrity in publication but also loss the trust of the people of the institution, the nation, and the world. The aim of this review article is to aware stakeholders specially novice reviewers about the peer review system. Beginners will understand how to review an article and they can justify better action choices in dealing with reviewing an article.